Gradient Ricci–Yamabe Soliton on Twisted Product Manifolds. (30th June 2022) - Kim, Byung Hak; Choi, Jin Hyuk; Lee, Sang Deok; Han, Chang Yong
Abstract : In this paper, we study the twisted product manifolds with gradient Ricci–Yamabe solitons. Then, we classify and characterize the warped product and twisted product spaces with gradient Ricci–Yamabe solitons. We also study the construction of the model space of gradient Ricci–Yamabe solitons in the Riemannian product manifolds and the warped product manifolds. Finally, we study the geometric characterization of the conformally flat twisted product manifolds with gradient Ricci–Yamabe solitons.